2005
DOI: 10.1038/modpathol.3800358
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary intestinal-type adenocarcinoma does not show enteric differentiation by immunohistochemical study

Abstract: Six cases of an unusual variant of primary pulmonary adenocarcinoma resembling colorectal and sinonasal adenocarcinoma are presented. Pulmonary intestinal-type adenocarcinoma occurs in elderly Caucasians and is associated with a histology characteristic of colorectal/enteric adenocarcinoma: a garland-like architecture with a 'gland in gland' periphery, central 'dirty' necrosis, and elongated stratified columnar cells, lacking significant goblet or signet ring differentiation. While a resemblance to intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 30 publications
2
57
0
Order By: Relevance
“…Some of the cases in our study showed some of the features described by Yousem 30 and Inamura 31 resembling colorectal carcinoma, but our series further expands the morphologic spectrum that these tumors can display. This is of importance for differential diagnosis as tumors other than colorectal adenocarcinomas demonstrating a prominent cribriform growth pattern are capable of metastasizing to the lung and can arise from diverse sites such as the gallbladder, 33 paranasal sinuses, 34 urinary bladder, 35 breast, 11 prostate, 10 pancreas, 36 salivary glands, 37 thyroid, 38 sweat glands, stomach, ovary, 39 uterus, and endocervix.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Some of the cases in our study showed some of the features described by Yousem 30 and Inamura 31 resembling colorectal carcinoma, but our series further expands the morphologic spectrum that these tumors can display. This is of importance for differential diagnosis as tumors other than colorectal adenocarcinomas demonstrating a prominent cribriform growth pattern are capable of metastasizing to the lung and can arise from diverse sites such as the gallbladder, 33 paranasal sinuses, 34 urinary bladder, 35 breast, 11 prostate, 10 pancreas, 36 salivary glands, 37 thyroid, 38 sweat glands, stomach, ovary, 39 uterus, and endocervix.…”
Section: Discussionmentioning
confidence: 71%
“…29 The tumors were characterized by a predominant component of neoplastic tall columnar cells admixed with goblet cells and Paneth cells, with occasional features of neuroendocrine differentiation. More recently, pulmonary intestinal-type adenocarcinomas have also been described by Yousem 30 and by Inamura. 31 The tumors described by Yousem were characterized by a garland-like architecture, central 'dirty' necrosis, and stratified tall columnar cells lacking significant goblet cell or signet-ring features lining the glands.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…CDX2 is expressed in a high proportion of colorectal carcinomas (61-100%) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] whereas the reported range of expression in primary ovarian mucinous tumors (the majority reported being carcinomas) is broad (0-100%). 3,4,[7][8][9][11][12][13][14][15][16]19,22,23 Most studies have evaluated CDX2 and CK20 in ovarian mucinous tumors as independent markers; 7,9,12,14,16 very few studies have addressed coordinate expression with CK7 22,23 and none has performed an analysis of coordinate expression profiles directly comparing the performance of CDX2 and CK20, when combined with CK7, in the same group of tumors.…”
mentioning
confidence: 99%
“…Immunohistochemical markers can reliably differentiate between primary lesions at both sites, as lung adenocarcinomas express thyroid transcription factor-1 (TTF-1) and cytokeratin 7 (CK7) but not cytokeratin 20 (CK20) or CDX-2, whereas primary colon adenocarcinomas express CK20 and CDX-2 but not TTF-1 or CK7. [8] One study demonstrates that a combination of TTF-1+, CK7+, CK20-is highly specific for lung adenocarcinoma (p < .001), and TTF-1-, CK7-, CK20+ is extremely specific for gastrointestinal adenocarcinoma (p < .001). [9] This case occurred prior to the development of these markers.…”
Section: Discussionmentioning
confidence: 99%